A cohort study of the effects of social support on cerebral cardiovascular disease in subjects with metabolic syndrome - Kim, Sung-Kyung; Jeong, Yong Whi; Kang, Dae Ryong; Kim, Jang Young; Lee, Hunju; Koh, Sang-baek (PloS one, 2024)
Previous studies have extensively examined the relationship between social support and various health outcomes. However, little is known about the distinct longitudinal associations between perceived social support and the development of cardiovascular events in patients with metabolic syndrome. In this cohort study, we investigated whether the levels of perceived social support in patients with metabolic syndrome were associated with an increased risk of cerebrovascular and cardiovascular events. The level of social support was assessed using the Medical Outcomes Study-Social Support Survey (MOS-SSS) in 2,721 individuals living in Wonju and Pyeongchang, South Korea. The presence of metabolic syndrome was determined by physical measurements and blood tests, and the occurrence of cerebral cardiovascular disease in relation to the presence of metabolic syndrome and the level of social support was analyzed using Cox proportional-hazards models. The median follow-up period was 2,345 days (2,192-2,618). Overall, in the group with metabolic syndrome and low social support, low social support was associated with an increased risk of later cerebral cardiovascular events; in this group, the hazard ratio after adjusting for confounding variables was 1.97 times (95% confidence interval, 1.01-3.85) higher than that in the group without metabolic syndrome and low social support. This study shows, for the first time, that the level of social support is a risk factor for preventing cerebral cardiovascular disease in patients with metabolic syndrome and suggests that social support status should be incorporated into multifactorial risk assessment and intervention procedures to prevent metabolic syndrome and cerebral cardiovascular disease.